Uncoupled nitric oxide synthase activity promotes colorectal cancer progression - Alam, Asim; Smith, Steven C.; Gobalakrishnan, Sundaresan; McGinn, Mina; Yakovlev, Vasily A.; Rabender, Christopher S. (Frontiers in Oncology, 2023)
Increased levels of reactive oxygen/nitrogen species are one hallmark of chronic inflammation contributing to the activation of pro-inflammatory/proliferative pathways. In those cancers analyzed, the tetrahydrobiopterin:dihydrobiopterin ratio is lower than that of the corresponding normal tissue leading to uncoupled nitric oxide synthase activity and increased generation of reactive oxygen/ nitrogen species. Previously we demonstrated that prophylactic treatment with sepiapterin, a salvage pathway precursor of tetrahydrobiopterin, prevents dextran sodium sulfate induced colitis in mice and associated azoxymethane-induced colorectal cancer. Herein we report that increasing the tetrahydrobiopterin:dihydrobiopterin ratio and recoupling nitric oxide synthase with sepiapterin in the colon cancer cell lines, HCT116 and HT29, inhibits their proliferation and enhances cell death in part by Akt/GSK-3β mediated down-regulation of β-catenin. Therapeutic oral gavage with sepiapterin of mice bearing azoxymethane/dextran sodium sulfate induced colorectal cancer decreased metabolic uptake of [18F]-fluorodeoxyglucose and enhanced apoptosis 9-fold in these tumors. Immunohistochemical analysis of both mouse and human tissues indicated down-regulated expression of key enzymes in tetrahydrobiopterin biosynthesis in the colorectal cancer tumors. Human stage 1 colon tumors exhibited a significant decrease in the expression of quinoid dihydropteridine reductase, a key enzyme involved in recycling tetrahydrobiopterin suggesting a potential mechanism for the reduced tetrahydrobiopterin:dihydrobiopterin ratio in these tumors. In summary, sepiapterin treatment of colorectal cancer cells increases the tetrahydrobiopterin:dihydrobiopterin ratio, recouples nitric oxide synthase, and reduces tumor growth. We conclude that nitric oxide synthase coupling may provide a useful therapeutic target for treating patients with colorectal cancer.